A methodology for calculating individual indicators of tourism activity - Kyfyak, Vasyl; Kyfyak, Olexander (Turyzm/Tourism, 2018)
The purpose of the article is to find modern approaches for calculating the quantity of given characteristic features and accompanying tourist services and goods purchased by tourists, to determine the number of tourists visiting a city and forecasting the volume of travel services for the future. Solutions to the tasks set out in the article have been carried out with the help of both general academic and specialist research methods: analysis and synthesis, systematization and generalization, expert evaluation and extrapolation. Using the example of the city of Chernivtsi (Ukraine) the number of tourists visiting the city has been determined, the volume of services rendered and the average annual growth rate of tourism service implementation over the last five years has been calculated contributing to forecasting the volume of service delivery for the future.